Obstacles to using the Laboratory in Teaching Physics from the Point of View of The Physics Secondary School Teachers in the Central District Directorates in Jordan - AL-Labadi, Nadia Jaber (Journal of Educational and Psychological Sciences, 2019)
This study aimed at identifying the obstacles that face Physic teachers while using the laboratories in teaching high school stages in the Central District Directorates in Jordan, as the researcher conducted an analytical survey through distributing a questioner including five dimensions, which are; the laboratory technician, tools and machineries, physics syllabus and school’s schedules, librarian and teacher and students. The random sample consisted of a number (90) are all male and female teachers high school stage physic teachers in the Central District Directorates. The findings of the study showed that the most challenging obstacles were as followed using the laboratory had the mean (3.86), physics syllabus and school’s schedule had the mean (3.85), librarian and teacher had the mean (3.77), students had the mean (3.57) and at the end tools and machineries had the mean (3.51). All of which are rated (high). Therefore, there was not any statistical significant among all the means that hinder using laboratories among high school physic teachers’ attitudes in the Central District Directorates due to the limitation of teachers’ experiences. According to the study there were number of recommendations in order to overcome the obstacles and difficulties of using the laboratory by physic teachers in Jordan ’s schools in general. The necessity of providing the following requirements such as having big laboratory in each school with a special lab had the mean (3.77), the needed instruments, supplying electricity and water, gas and safety conditions. Also, shorting the number of students to accommodate the space of labs. Supervisors visits should be carefully scheduled to lead teachers as well as trainings and workshops to increase teacher profitability. Further studies are recommended on the role of schools administrations in making school labs more effective and another study on virtual labs in helping physic teacher making experiments and making labs experiments guidance alongside with automated exams